Kesiapan Guru dalam Penilaian Autentik pada Kurikulum Merdeka Pembelajaran IPAS di Sekolah Dasar - Pebriyanti, Maisarah; Siagian, Fitri Nauli; Tabroni (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
This research explains the teacher's readiness in implementing authentic assessment in the Independent Curriculum which includes the preparation and implementation stages in the natural and social sciences learning evaluation process. The aims of this research are (1) to describe the readiness and understanding of teachers and principals at State Elementary School 58 Jambi City regarding the Independent Curriculum in authentic assessment, especially natural and social sciences learning; (2) analyze the implementation of the Merdeka Curriculum in authentic assessment of natural and social sciences learning. This research is qualitative with a descriptive approach, using phenomenological methods. The data source involved the school principal and class IV homeroom teacher at SD Negeri 58 Jambi City. Data collection techniques include interviews, observation, and documentation, using data analysis techniques using the model from Hubenman, and Saldana, namely data collection, data condensation, data presentation, and data/conclusion verification as well as data validity using triangulation techniques. The research results show that (1) Teachers and school principals have prepared themselves and understand authentic assessment in the Merdeka Curriculum, especially in natural and social sciences learning; (2) Teachers have implemented authentic assessment in the Independent Curriculum through comprehensive and continuous evaluation of Attitudes, Competencies and Skills. Implementation of authentic assessments based on knowledge competencies in science subjects using written techniques, oral tests and assignments. Attitude competency assessment utilizes observation techniques, self- assessment, peer assessment, and journal assessment. Meanwhile, authentic assessment based on skill competency is carried out through performance assessment techniques, project assessment, product assessment and portfolio assessment.